Pengaruh Psychological Ownership Dan Budaya Organisasi Terhadap Berbagi Pengetahuan Pada UMKM Tipe Perusahaan Keluarga Di Jawa Timur - Khoirur Rozaq (Pusat Riset dan Inovasi Nasional, 2022)
The business concept at this time has changed exponentially, where innovation and the company's ability to change become the main point to gaining a competitive advantage. Knowledge is essential to obtaining organizational innovation and creativity, where the role of knowledge sharing is essential. Predictor knowledge sharing in family companies involves many elements of psychology and the surrounding environment. This research journal discusses more the form of influence caused by psychological ownership and organizational culture on knowledge sharing in MSMEs with the type of family company. These aspects are essential to get his immediate attention in the role of knowledge sharing, especially in family companies. In this study, the research method used is a quantitative research method, in which this method is used to determine the level of influence resulting from each variable using regression analysis. The research instrument used in this study is the form of a questionnaire which has three forms of variables, namely; (1) Psychological Ownership, (2) Organizational Culture, and (3) Knowledge Sharing. Each of these variables contains five statements, including a validity test and a reliability test whose significance level is <0.60 so that it is declared valid and reliable.Meanwhile, the population in this study was in a family company in East Java. The sample was taken in this analysis using a purposive sampling form of 150 people. The results are as follows; (1) Psychology Ownership affects the distribution of knowledge in MSMEs type of Family Companies in East Java; (2) There is an influence on Organizational Culture on Family Company Type MSMEs in East Java..